Inorganic high-strength artificial quartz stone and preparation method thereof

By alkali etching and grafting the basalt fibers, the modified basalt fibers and their composites were prepared, and mixed with cement and other materials as reinforcers, the problem of insufficient strength inorganic artificial quartz stone was solved, and the effect of high strength and simplified preparation process was achieved.

CN119707402AActive Publication Date: 2025-03-28XINYUN STONE (YUNFU) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411923921.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Due to the limited adhesion of cement, the existing inorganic artificial quartz stone has reduced the interface strength and a large space for improvement.

Method used

By alkaline corrosion of basalt fibers with a length of 3-5mm and grafting of sodium carboxymethylcellulose sodium, modified basalt fibers were prepared and combined with untreated basalt fibers. They were mixed with cement, quartz sand, quartz powder and other materials as reinforcement agents, and high-strength inorganic artificial quartz stone was produced by vacuum vibration forming.

Benefits of technology

It significantly improves the strength of inorganic artificial quartz stone, simplifies the preparation process, and makes it easy to achieve industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to inorganic high-strength artificial quartz stone and a preparation method thereof, and belongs to the technical field of artificial quartz stone. According to the preparation method, the basalt fiber with the length of 3-5 mm is creatively subjected to alkali corrosion of a sodium hydroxide solution and grafting of sodium carboxymethyl cellulose in sequence, so that the modified basalt fiber with the relatively short length is prepared, the modified basalt fiber is compounded with the basalt fiber which is not subjected to any treatment and has the length of 10-15 mm, and the composite material is obtained. Then silica fume, alunite and the composite basalt fiber which are in a certain mass ratio are used as reinforcing agents to be mixed with cement, quartz sand, quartz powder, a water reducing agent and deionized water, and the inorganic artificial quartz stone is obtained through conventional operations such as vibration molding and maintenance in a vacuum state. Meanwhile, the whole preparation process of the inorganic artificial quartz stone is simple in flow, and industrial production is easy to realize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of artificial quartz stone, and particularly relates to an inorganic high-strength artificial quartz stone and a preparation method thereof. Background Art

[0002] Artificial quartz stone is a plate made of cementitious materials, quartz sand, quartz powder and additives as main components, which is mixed, vacuumed under negative pressure, vibrated and formed in sequence. It has hard texture and dense structure, and has the characteristics of wear resistance, high temperature resistance and corrosion resistance that other decorative materials cannot match. Among them, if classified according to the type of cementitious materials, artificial quartz stone can be divided into inorganic artificial quartz stone (cement as cementitious material) and organic artificial quartz stone (resin as cementitious material). Compared with organic artificial quartz stone, inorganic artificial quartz stone has less emission of volatile organic pollutants, is more environmentally friendly, and conforms to the concept of green development. However, the existing inorganic artificial quartz stone still has certain disadvantages that limit its actual application effect. This is because when cement is used as a cementitious material, it often faces the problem of limited bonding force. Cement is not as good as resin in adhesion, resulting in a decrease in interface strength, which ultimately results in the strength of the inorganic artificial quartz stone still having a lot of room for improvement. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide an inorganic high-strength artificial quartz stone and a preparation method thereof. The present invention creatively performs alkaline etching with sodium hydroxide solution and grafting with sodium carboxymethyl cellulose on basalt fibers with a length of 3-5 mm in sequence, thereby preparing a modified basalt fiber with a relatively short length, and then composites the modified basalt fiber with a basalt fiber with a length of 10-15 mm that has not been treated in any way to form a composite basalt fiber, and then uses silica fume, alum stone and composite basalt fiber in a certain mass ratio as reinforcing agents, mixes them with cement, quartz sand, quartz powder, water reducing agent and deionized water, and then obtains an inorganic artificial quartz stone through conventional operations such as vibration molding and curing under a vacuum state, which has very excellent strength. At the same time, the present invention has a simple process in the entire preparation process of the inorganic artificial quartz stone, and is easy to realize industrial production.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] The invention discloses an inorganic high-strength artificial quartz stone, which is prepared from cement, quartz sand, quartz powder, a water reducing agent, a reinforcing agent and deionized water; the reinforcing agent comprises silica fume, alum stone and composite basalt fiber.

[0006] As a preferred technical solution of the present invention, the mass ratio of the cement, the quartz sand, the quartz powder, the water reducer, the strengthener and the deionized water is 30-32:35:25-30:0.2-0.3:9:8-10.

[0007] As a preferred technical solution of the present invention, the mass ratio of the silica fume, the alunite and the composite basalt fiber is 3:2:3-4.

[0008] As a preferred technical solution of the present invention, the cement is silicate cement.

[0009] As a preferred technical solution of the present invention, the quartz sand is continuously graded quartz sand; the particle size distribution of the continuously graded quartz sand is 10-20 mesh, 20-40 mesh, 40-70 mesh and 70-140 mesh, and the mass ratio is 3-3.2:3.5:2:1.5.

[0010] As a preferred technical solution of the present invention, the particle size of the quartz powder is 300-320 mesh.

[0011] As a preferred technical solution of the present invention, the water reducer is a polycarboxylate water reducer.

[0012] As a preferred technical solution of the present invention, the particle size of the alunite is 200-300 mesh.

[0013] As a preferred technical solution of the present invention, the composite basalt fiber is prepared by the following steps:

[0014] Step A: adding 2-3 parts by weight of basalt fiber A to 80 parts by weight of sodium hydroxide solution, stirring at 40-60° C. for 1 hour, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60-80° C. until constant weight, to obtain component A;

[0015] Step B: adding 2-3 parts by weight of sodium carboxymethyl cellulose and 4-5 parts by weight of component A to 80 parts by weight of deionized water, stirring at 60-65° C. for 2 hours, filtering, taking the filter residue, washing it with deionized water, and finally vacuum drying it at 60-80° C. until constant weight, to obtain modified basalt fiber A;

[0016] Step C: The modified basalt fiber A and the basalt fiber B are mixed at a mass ratio of 1-1.2:2, and the preparation is completed.

[0017] Furthermore, the concentration of the sodium hydroxide solution in step A is 0.5-0.7 mol / L.

[0018] Furthermore, in step A, the diameter of the basalt fiber A is 10-15 μm; the length of the basalt fiber A is 3-5 mm; and the tensile strength of the basalt fiber A is 3500-4000 MPa.

[0019] Furthermore, in step C, the diameter of the basalt fiber B is 10-15 μm; the length of the basalt fiber B is 10-15 mm; and the tensile strength of the basalt fiber B is 3500-4000 MPa.

[0020] A method for preparing inorganic high-strength artificial quartz stone, the preparation method comprising the following steps:

[0021] Add cement and water reducing agent to deionized water, then stir for 2-3 minutes at room temperature, then add quartz sand, quartz powder and strengthening agent, continue to stir for 3-5 minutes at room temperature, pour into the mold, vibrate and form using a vibration compaction molding machine under vacuum, demold, cure, naturally cool to room temperature, polish, cut, and the preparation is complete.

[0022] As a preferred technical solution of the present invention, the vacuum degree of the vacuum state is -0.1 MPa.

[0023] As a preferred technical solution of the present invention, the working parameters of the vibration compaction molding machine are as follows: the vibration frequency is controlled at 50 Hz, the static pressure is controlled at 40-50 kg, and the time is controlled at 5 minutes.

[0024] As a preferred technical solution of the present invention, the curing refers to curing at 35-40°C for 7 days.

[0025] Beneficial effects of the present invention:

[0026] (1) The present invention creatively performs alkaline etching with sodium hydroxide solution and grafting with sodium carboxymethyl cellulose on basalt fibers with a length of 3-5 mm in sequence, thereby preparing a modified basalt fiber with a relatively short length, and then composites the modified basalt fiber with a basalt fiber with a length of 10-15 mm that has not been treated in any way to form a composite basalt fiber. Then, silica fume, alum stone and composite basalt fiber in a certain mass ratio are used as reinforcing agents, and are mixed with cement, quartz sand, quartz powder, water reducing agent and deionized water. After conventional operations such as vibration molding and curing under a vacuum state, an inorganic artificial quartz stone having excellent strength is obtained. At the same time, the present invention has a simple process in the entire preparation process of the inorganic artificial quartz stone, and is easy to realize industrial production.

[0027] (2) The present invention creatively performs alkaline etching with sodium hydroxide solution and grafting with sodium carboxymethyl cellulose on basalt fibers with a length of 3-5 mm in sequence. On the one hand, sodium hydroxide, as a strong base, can etch the surface of the basalt fibers to form a certain groove structure. On the other hand, sodium carboxymethyl cellulose contains a large number of carboxylate ions, which can react with the metal ions on the surface of the basalt fibers to complete the grafting through the formation of covalent bonds, thereby preparing a modified basalt fiber with a relatively short length, which is used as a reinforcing agent with silica fume, alum stone and basalt fibers with a length of 10-15 mm without any treatment, thereby giving the final inorganic artificial quartz stone excellent strength; silica fume contains highly chemically active silicon dioxide, which can undergo secondary hydration with the hydration product of cement to generate amorphous secondary hydration products, thereby enhancing the interface strength to a certain extent. Alunite can promote the formation of needle-shaped ettringite in the system, and the interfacial bonding force is further improved by interweaving the amorphous secondary hydration product with the needle-shaped ettringite. At the same time, the introduction of modified basalt fiber can not only better fit and fill the tiny cracks inside the system with its own small size and groove structure to achieve the interface repair effect, but also because its surface contains a large number of carboxylate ions, it can also produce organic-metal coordination with the secondary hydration product, promote the formation of secondary hydration products on its surface, and then play an excellent synergistic effect to obtain a better interface repair effect (although the polycarboxylate water-reducing agent also contains a large number of carboxylate ions, it is different from the modified basalt fiber of the present invention in that the polycarboxylate water-reducing agent mainly adheres to the surface of cement particles to play a water-reducing effect). As for the basalt fiber with a length between 10-15 mm, it has a certain reinforcement effect as a whole. DETAILED DESCRIPTION

[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0029] The silicate cement in all the embodiments and comparative examples of the present invention is purchased directly from the market, purchased from Jiangxi Yinshan Super Materials Technology Co., Ltd., and the model is Yinshan brand P.W42.5 grade; the polycarboxylic acid water reducer is purchased directly from the market, purchased from Shandong Yuncheng Huihuang New Building Materials Technology Co., Ltd., with a solid content of 20%; the sodium carboxymethyl cellulose is purchased directly from the market, purchased from Shandong Weifang Li Te Composite Materials Co., Ltd., and the model is IH8; the silica fume is purchased directly from the market, purchased from Gansu Sanyuan Silicon Materials Co., Ltd., and the model is SF88.

[0030] Example 1

[0031] The invention discloses an inorganic high-strength artificial quartz stone, which is prepared from cement, quartz sand, quartz powder, a water reducing agent, a reinforcing agent and deionized water; the reinforcing agent comprises silica fume, alum stone and composite basalt fiber.

[0032] The mass ratio of the cement, the quartz sand, the quartz powder, the water reducing agent, the strengthening agent and the deionized water is 30:35:25:0.2:9:8.

[0033] The mass ratio of the silica fume, the alunite and the composite basalt fiber is 3:2:3.

[0034] The cement is silicate cement.

[0035] The quartz sand is continuously graded quartz sand; the particle size distribution of the continuously graded quartz sand is 10-20 mesh, 20-40 mesh, 40-70 mesh and 70-140 mesh, and the mass ratio is 3:3.5:2:1.5.

[0036] The particle size of the quartz powder is 300 meshes.

[0037] The water reducer is a polycarboxylate water reducer.

[0038] The particle size of the alum stone is 200 meshes.

[0039] The composite basalt fiber is prepared by the following steps:

[0040] Step A: adding 2 parts by weight of basalt fiber A to 80 parts by weight of sodium hydroxide solution, stirring at 40° C. for 1 hour, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60° C. until constant weight, to obtain component A;

[0041] Step B: adding 2 parts by weight of sodium carboxymethyl cellulose and 4 parts by weight of component A to 80 parts by weight of deionized water, stirring at 60° C. for 2 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60° C. until constant weight, to obtain modified basalt fiber A;

[0042] Step C: The modified basalt fiber A and the basalt fiber B are mixed in a mass ratio of 1:2, and the preparation is completed.

[0043] The concentration of the sodium hydroxide solution in step A is 0.5 mol / L.

[0044] In step A, the diameter of the basalt fiber A is 10 μm; the length of the basalt fiber A is 3 mm; and the tensile strength of the basalt fiber A is 3500 MPa.

[0045] In step C, the diameter of the basalt fiber B is 10 μm; the length of the basalt fiber B is 10 mm; and the tensile strength of the basalt fiber B is 3500 MPa.

[0046] A method for preparing inorganic high-strength artificial quartz stone, the preparation method comprising the following steps:

[0047] Add cement and water reducing agent to deionized water, then stir for 2 minutes at room temperature, then add quartz sand, quartz powder and strengthening agent, continue to stir for 3 minutes at room temperature, pour into the mold, vibrate and form using a vibration compaction molding machine under vacuum, demold, cure, naturally cool to room temperature, polish, cut, and the preparation is complete.

[0048] The vacuum degree of the vacuum state is -0.1 MPa.

[0049] The working parameters of the vibration compaction molding machine are as follows: the vibration frequency is controlled at 50 Hz, the static pressure is controlled at 40 kg, and the time is controlled at 5 min.

[0050] The curing refers to curing at 35° C. for 7 days.

[0051] Example 2

[0052] The invention discloses an inorganic high-strength artificial quartz stone, which is prepared from cement, quartz sand, quartz powder, a water reducing agent, a reinforcing agent and deionized water; the reinforcing agent comprises silica fume, alum stone and composite basalt fiber.

[0053] The mass ratio of the cement, the quartz sand, the quartz powder, the water reducing agent, the strengthening agent and the deionized water is 32:35:30:0.3:9:10.

[0054] The mass ratio of the silica fume, the alunite and the composite basalt fiber is 3:2:4.

[0055] The cement is silicate cement.

[0056] The quartz sand is continuously graded quartz sand; the particle size distribution of the continuously graded quartz sand is 10-20 mesh, 20-40 mesh, 40-70 mesh and 70-140 mesh, and the mass ratio is 3.2:3.5:2:1.5.

[0057] The particle size of the quartz powder is 320 meshes.

[0058] The water reducer is a polycarboxylate water reducer.

[0059] The particle size of the alum stone is 300 meshes.

[0060] The composite basalt fiber is prepared by the following steps:

[0061] Step A: adding 3 parts by weight of basalt fiber A to 80 parts by weight of sodium hydroxide solution, stirring at 60° C. for 1 hour, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 80° C. until constant weight, to obtain component A;

[0062] Step B: adding 3 parts by weight of sodium carboxymethyl cellulose and 5 parts by weight of component A to 80 parts by weight of deionized water, stirring at 65° C. for 2 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 80° C. until constant weight, to obtain modified basalt fiber A;

[0063] Step C: The modified basalt fiber A and the basalt fiber B are mixed at a mass ratio of 1.2:2, and the preparation is completed.

[0064] The concentration of the sodium hydroxide solution in step A is 0.7 mol / L.

[0065] In step A, the diameter of the basalt fiber A is 15 μm; the length of the basalt fiber A is 5 mm; and the tensile strength of the basalt fiber A is 4000 MPa.

[0066] In step C, the diameter of the basalt fiber B is 15 μm; the length of the basalt fiber B is 15 mm; and the tensile strength of the basalt fiber B is 4000 MPa.

[0067] A method for preparing inorganic high-strength artificial quartz stone, the preparation method comprising the following steps:

[0068] Add cement and water reducing agent to deionized water, then stir for 3 minutes at room temperature, then add quartz sand, quartz powder and strengthening agent, continue to stir for 5 minutes at room temperature, pour into the mold, vibrate and form using a vibration compaction molding machine under vacuum, demold, cure, naturally cool to room temperature, polish, cut, and the preparation is complete.

[0069] The vacuum degree of the vacuum state is -0.1 MPa.

[0070] The working parameters of the vibration compaction molding machine are as follows: the vibration frequency is controlled at 50 Hz, the static pressure is controlled at 50 kg, and the time is controlled at 5 min.

[0071] The curing refers to curing at 40° C. for 7 days.

[0072] Example 3

[0073] The invention discloses an inorganic high-strength artificial quartz stone, which is prepared from cement, quartz sand, quartz powder, a water reducing agent, a reinforcing agent and deionized water; the reinforcing agent comprises silica fume, alum stone and composite basalt fiber.

[0074] The mass ratio of the cement, the quartz sand, the quartz powder, the water reducing agent, the strengthening agent and the deionized water is 31:35:27:0.25:9:9.

[0075] The mass ratio of the silica fume, the alunite and the composite basalt fiber is 3:2:3.5.

[0076] The cement is silicate cement.

[0077] The quartz sand is continuously graded quartz sand; the particle size distribution of the continuously graded quartz sand is 10-20 mesh, 20-40 mesh, 40-70 mesh and 70-140 mesh, and the mass ratio is 3.1:3.5:2:1.5.

[0078] The particle size of the quartz powder is 310 meshes.

[0079] The water reducer is a polycarboxylate water reducer.

[0080] The particle size of the alum stone is 250 meshes.

[0081] The composite basalt fiber is prepared by the following steps:

[0082] Step A: adding 2.5 parts by weight of basalt fiber A to 80 parts by weight of sodium hydroxide solution, stirring at 50° C. for 1 hour, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 70° C. until constant weight, to obtain component A;

[0083] Step B: adding 2.5 parts by weight of sodium carboxymethyl cellulose and 4.5 parts by weight of component A to 80 parts by weight of deionized water, stirring at 63° C. for 2 hours, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 70° C. until constant weight, to obtain modified basalt fiber A;

[0084] Step C: The modified basalt fiber A and the basalt fiber B are mixed at a mass ratio of 1.1:2, and the preparation is completed.

[0085] The concentration of the sodium hydroxide solution in step A is 0.6 mol / L.

[0086] In step A, the diameter of the basalt fiber A is 12 μm; the length of the basalt fiber A is 4 mm; and the tensile strength of the basalt fiber A is 3500 MPa.

[0087] In step C, the diameter of the basalt fiber B is 12 μm; the length of the basalt fiber B is 11 mm; and the tensile strength of the basalt fiber B is 3500 MPa.

[0088] A method for preparing inorganic high-strength artificial quartz stone, the preparation method comprising the following steps:

[0089] Add cement and water reducing agent to deionized water, then stir for 2.5 minutes at room temperature, then add quartz sand, quartz powder and strengthening agent, continue to stir for 4 minutes at room temperature, pour into the mold, vibrate and form using a vibration compaction molding machine under vacuum, demold, cure, naturally cool to room temperature, polish, cut, and the preparation is complete.

[0090] The vacuum degree of the vacuum state is -0.1 MPa.

[0091] The working parameters of the vibration compaction molding machine are as follows: the vibration frequency is controlled at 50 Hz, the static pressure is controlled at 45 kg, and the time is controlled at 5 min.

[0092] The curing refers to curing at 38°C for 7 days.

[0093] Comparative Example 1

[0094] Based on Example 3, the silica fume was replaced with an equal weight of alunite, and the rest remained unchanged.

[0095] Comparative Example 2

[0096] On the basis of Example 3, alunite was replaced with composite basalt fiber of equal weight, and the rest remained unchanged.

[0097] Comparative Example 3

[0098] On the basis of Example 3, the composite basalt fiber was replaced with silica fume of equal weight, and the rest remained unchanged.

[0099] Comparative Example 4

[0100] On the basis of Example 3, the composite basalt fiber was replaced with modified basalt fiber A of equal weight, and the rest remained unchanged.

[0101] Comparative Example 5

[0102] On the basis of Example 3, the composite basalt fiber was replaced with basalt fiber B of equal weight, and the rest remained unchanged.

[0103] Comparative Example 6

[0104] On the basis of Example 3, the length of the basalt fiber A is changed from 4 mm to 11 mm, and the rest remain unchanged.

[0105] Comparative Example 7

[0106] On the basis of Example 3, the length of the basalt fiber A is changed from 4 mm to 11 mm, and the length of the basalt fiber B is changed from 11 mm to 4 mm, and the rest remain unchanged.

[0107] Comparative Example 8

[0108] On the basis of Example 3, the sodium hydroxide solution was replaced by an equal weight of deionized water, and the rest remained unchanged.

[0109] Comparative Example 9

[0110] On the basis of Example 3, the sodium carboxymethyl cellulose was replaced by an equal weight of deionized water, and the rest remained unchanged.

[0111] Test Example 1

[0112] Strength test:

[0113] The inorganic high-strength artificial quartz stones prepared in Example 3 and Comparative Examples 1-9 were respectively subjected to bending strength tests according to standard GB / T35160.2-2017, wherein the specifications of the samples were all 200 mm*50 mm*50 mm.

[0114] Table 1. Strength test results

[0115] Bending strength / MPa Example 3 19.8 Comparative Example 1 15.2 Comparative Example 2 16.1 Comparative Example 3 15.8 Comparative Example 4 16.7 Comparative Example 5 16.2 Comparative Example 6 17.1 Comparative Example 7 17.6 Comparative Example 8 17.0 Comparative Example 9 17.4

[0116] From the comparison between Test Example 1, Example 3 and Comparative Examples 1-9, it can be seen that the inorganic artificial quartz stone prepared by the present invention has more excellent strength.

[0117] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. An inorganic high-strength artificial quartz stone, characterized in that: The inorganic high-strength artificial quartz stone is prepared from cement, quartz sand, quartz powder, water reducing agent, reinforcing agent and deionized water; the reinforcing agent includes silica fume, alum stone and composite basalt fiber.

2. The inorganic high-strength artificial quartz stone according to claim 1, characterized in that: The mass ratio of the cement, the quartz sand, the quartz powder, the water reducing agent, the strengthening agent and the deionized water is 30-32:35:25-30:0.2-0.3:9:8-10.

3. The inorganic high-strength artificial quartz stone according to claim 1, characterized in that: The mass ratio of the silica fume, the alunite and the composite basalt fiber is 3:2:3-4.

4. The inorganic high-strength artificial quartz stone according to claim 1, characterized in that: The cement is silicate cement.

5. The inorganic high-strength artificial quartz stone according to claim 1, characterized in that: The particle size of the alum stone is 200-300 meshes.

6. The inorganic high-strength artificial quartz stone according to claim 1, characterized in that: The composite basalt fiber is prepared by the following steps: Step A: adding 2-3 parts by weight of basalt fiber A to 80 parts by weight of sodium hydroxide solution, stirring at 40-60° C. for 1 hour, filtering, taking the filter residue, washing with deionized water, and finally vacuum drying at 60-80° C. until constant weight, to obtain component A; Step B: adding 2-3 parts by weight of sodium carboxymethyl cellulose and 4-5 parts by weight of component A to 80 parts by weight of deionized water, stirring at 60-65° C. for 2 hours, filtering, taking the filter residue, washing it with deionized water, and finally vacuum drying it at 60-80° C. until constant weight, to obtain modified basalt fiber A; Step C: The modified basalt fiber A and the basalt fiber B are mixed at a mass ratio of 1-1.2:2, and the preparation is completed.

7. The inorganic high-strength artificial quartz stone according to claim 6, characterized in that: The concentration of the sodium hydroxide solution in step A is 0.5-0.7 mol / L.

8. The inorganic high-strength artificial quartz stone according to claim 6, characterized in that: In step A, the diameter of the basalt fiber A is 10-15 μm; the length of the basalt fiber A is 3-5 mm; and the tensile strength of the basalt fiber A is 3500-4000 MPa.

9. The inorganic high-strength artificial quartz stone according to claim 6, characterized in that: In step C, the diameter of the basalt fiber B is 10-15 μm; the length of the basalt fiber B is 10-15 mm; and the tensile strength of the basalt fiber B is 3500-4000 MPa.

10. A method for preparing the inorganic high-strength artificial quartz stone according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: Add cement and water reducing agent to deionized water, then stir for 2-3 minutes at room temperature, then add quartz sand, quartz powder and strengthening agent, continue to stir for 3-5 minutes at room temperature, pour into the mold, vibrate and form using a vibration compaction molding machine under vacuum, demold, cure, naturally cool to room temperature, polish, cut, and the preparation is complete.

Citation Information

Patent Citations

  • Basalt fiber reactive powder concrete and preparation method thereof

    CN111747709A

  • Shrinkage compensation composite material based on modified alunite tailings and preparation method thereof

    CN114455904A

  • Modified basalt fiber inorganic artificial stone and preparation method thereof

    CN114890736A

  • Continuous basalt fiber surface modification method based on sodium hydroxide solution

    CN118930072A

  • Silicate cement for artificial marble

    CN86102766A